Structural change and international migration in East Asia adjusting to labour scarcity - Athukorala, Prema-chandra; Manning, Chris (Oxford University Press, 1999)
This text provides a systematic analysis of the rapid growth of international labour migration in East Asia. It examines the increase in international labour migration in relation to growth and structural change in labour-receiving countries.